Pemberdayaan Ibu Rumah Tangga melalui Pelatihan Kewirausahaan: Kreasi Scrunchie dan Inovasi Bola Singkong Lumer - Safitri, Noor Laila; Oktaviani, Riska Tri; Syaharani, Nabila Putri; Laila, Anisa Nur; Ahsan, Fahri Sirajuddin; Cahyaningrum, Gian; Putri, Ika Marsandra; Romadhon, Ilham Risky; Aini, Nafisah Nur; Janah, Nuur Laelatul; Rifa’i, Ridwan Mahfudz; Nuruzzain, Tsalitsa; Saidah, Umi; Abdilah, Mokhamad Azis Aji (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
Entrepreneurship training is one of the efforts to empower homemakers in improving economic independence within the family. This activity is driven by the importance of women’s roles in supporting household income through creative businesses based on local potential, such as utilising fabric scraps and traditional food ingredients. The training was conducted at the PKK Hall of RT 01 RW 05 Dukuh Plosowangi Wetan, involving 27 PKK members. The method used in this community service activity was Participatory Action Research (PAR), consisting of observation, action (material delivery and practice), and active participation from the participants. The training focused on making scrunchies from fabric scraps and molten cassava balls using natural materials available in the surrounding environment. The results showed that the training ran successfully, as seen from the participants’ enthusiasm and their improved skills in producing both products. The average evaluation score given by participants reached 4.20 on a scale of 1 to 5. Interestingly, one of the participants had already implemented the training results by producing and selling molten cassava balls through a consignment system at nearby stores. This activity has had a positive impact in terms of enhancing skills, boosting entrepreneurial spirit, and raising awareness about utilising waste and local materials for creative business. The training is expected to be a catalyst for the growth of micro-home enterprises within the village community.